The integration proces of the Lower Moesian areas - Duch, Michał (Instytut Kultury Europejskiej UAM, 2017)
The objective of this article is to provide a short presentation of the integration process of the areas that formed Lower Moesia. The author aims to present select methods implemented by the Romans in order to place the discussed territories under their complete control. The main differences between the individual parts of Lower Moesia have also been indicated in the article, as well as the ways in which they mutually supplemented each other, ultimately composing a cohesive whole.
Lower Moesia was amalgamated from territories whose degree of urbanization varied. The line of the Danube was dominated by the Roman army and civilian settlers who were associated with the army in one way or another. As for the interior of the province, there were the two major urban centres of Nicopolis ad Istrum and Marcianopolis, as well as Montana, Abrittus and environs of the present-day Šumen. The urban potential of eastern Lower Moesia stemmed from the existence of Greek cities, such as Olbia, Tyras, Histria, Tomis, Callatis, Dionysopolis, Odessos, which maintained their separate character, just as the area of Dobruja. In each of those territories the Romans implemented a different strategy of integration. Along the Danube, Rome established tribal administrative districts (civitates, territoria). Simultaneously, civilian settlements sprang up in the vicinity of military encampments; in time, some of those were granted the status of municipium and colony (Oescus). In Dobruja, the Romans effected an administrative reorganization of the Greek cities and supported intensive colonization, whose most palpable and widespread manifestation was establishing villages which emulated the Roman pattern. The so-called interior represented a highly diverse area. Before Trajan initiated the construction of Nicopolis ad Istrum and Marcianopolis, Thracian strategiai governed by local aristocrats were to be found there. Rome dissolved them gradually and pursued urbanization undertakings there. Having founded both of the aforesaid cities, the Romans opted for a Greek model of their development, realizing that it would be more culturally familiar to Thracians than the Roman one. The pace of integration depended on the interests of Rome itself. The economically valuable mining areas were where Roman influence was brought to bear in the first place. For this reason, Montana was promptly and entirely subordinated to military administration, in order to secure its natural resources. The regions of Abrittus and Šumen were poorly urbanized, but the Romans recognized their substantial agricultural potential (Šumen in particular) establishing a number of imperial domains and land estates for lease, which then became a highly efficient logistical base for the army stationed on the Danube. In conclusion, although Lower Moesia was a relatively small province, stretching as it did along the Danube, it was a cohesive entity in terms of administration. Each part of the province played a particular role and proved to function in a manner that was complementary to the others
Keywords: Lower Moesia; administration; civitas; territory; integration; municpium